La desintegración familiar y su incidencia en el comportamiento agresivo de los niños y niñas del primer año de educación general básica de la escuela "Lauro Damerval Ayora" de la ciudad de Loja, en el periodo lectivo 2014- 2015 - Mendoza Pacheco, Patricia Margarita (2015)
This thesis refers to "FAMILY DECAY AND ITS IMPACT ON THE AGGRESSIVE BEHAVIOR OF CHILDREN FIRST YEAR OF GENERAL BASIC EDUCATION SCHOOL" Lauro Damerval AYORA "CITY Loja, for school year 2014 2015" conducted according to the provisions of the Academic System of the National University of Loja. He was raised as General Objective: To analyze family breakdown and its impact on the aggressive behavior of children in the first year of basic general education. The methods used for preparation of the present research work were: Scientific, Inductive, Deductive, Descriptive and Statistical Model, the same that served effectively help to achieve the proposed goal. The techniques and instruments used were: Survey aimed at parents or relatives of children in the first year of General Basic Education School Lauro Damerval Ayora City Loja, in order to analyze the Family Breakup and observation sheet applied to children of the First Year of General Basic Education School ¨Lauro Damerval Ayora¨ city of Loja, to determine the types of behavior. According to the results of the survey of parents is concluded that: There is a 31% of children living in dysfunctional homes, become clear that family 69% breakdown is incident on the aggressive behavior of these children. Analyzed the results of the Observation Form is concluded that: 61% of boys and girls surveyed have an Aggressive Behavior, 28% unaggressive, and 11% very aggressive. 53% of boys and girls surveyed have a Passive Behavior, 39% passive, and, the, 8% very passive. 53% of children surveyed have a Assertive Behavior, 39% very assertive, and 8% unassertive.